2020
DOI: 10.1101/2020.02.16.951475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of nanoscale antigen organization on B-cell activation probed using DNA origami

Abstract: Arraying vaccine immunogens in a multivalent form on the surface of virus-like particles is an important strategy used to enhance the efficacy of subunit vaccines. However, the impacts of antigen valency, spacing, and spatial organization on B cell triggering remain poorly understood. Here, we use DNA origami nanoparticles to create precise nanoscale organizations of a clinically-relevant HIV gp120 immunogen to systematically interrogate their impact on B cell triggering in vitro. We find that antigen dimers e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 42 publications
5
67
1
Order By: Relevance
“…Finally, to demonstrate the utility of our stabilization strategy for translational applications, we investigated its compatibility with DNA origami functionalization. Toward this end, we synthesized PB84 conjugated to 10 copies of the engineered HIV antigen eOD-GT8, using PNA:DNA hybridization, as previously described 14 . The functionalized two-helix wireframe assembly was subsequently coated with diamidine 5 and incubated with Ramos B cells recombinantly expressing an IgM-BCR specific for eOD-GT8 [54][55] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to demonstrate the utility of our stabilization strategy for translational applications, we investigated its compatibility with DNA origami functionalization. Toward this end, we synthesized PB84 conjugated to 10 copies of the engineered HIV antigen eOD-GT8, using PNA:DNA hybridization, as previously described 14 . The functionalized two-helix wireframe assembly was subsequently coated with diamidine 5 and incubated with Ramos B cells recombinantly expressing an IgM-BCR specific for eOD-GT8 [54][55] .…”
Section: Resultsmentioning
confidence: 99%
“…DNA nanostructures have further been deployed in a variety of preliminary studies as therapeutic delivery platforms. These applications include the controlled organization of antigens to activate B cells 14 , the delivery of siRNA [15][16] , CpG oligonucleotides 17 and small molecules drugs [18][19][20] . Logicgated nanorobots have been leveraged to to achieve controlled cargo release in vitro 21 and in vivo 1 .…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of interfaces will definitely help both experts and non-specialists to create their own DNA nano-objects. Importantly, the research group of Bathe et al has already shown that their designer wireframe DNA origami shapes may have an imminent biomedical application, as they created various precise multivalent arrangements of a clinically-relevant HIV gp120 immunogen on the virus-like DNA particles to systematically probe their impact on B cell triggering in vitro [94]. We strongly believe that all these versatile structures will find uses not only in biological research but also in assembling novel functional materials [95][96][97][98].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Significant attention has been devoted to the presentation of antigens on different scaffolds in a precisely defined geometry 45,77 , however the results of fusion with βannulus peptide, that apparently generates polydisperse but large oligomers, suggest that precise positioning may not be required, unless for the generation of desired natural-like arrangement of the epitopes, such as e.g. trimerization of viral protein domains.…”
Section: Immune Response Against the Scaffold In A Genetic Fusion Witmentioning
confidence: 99%
“…Presentation of the target antigen domain in the multimeric form may be accomplished by chemical conjugation of a viral protein domain to the nanoparticle or by a genetic fusion to the scaffold-forming polypeptide domain. Examples of the attachment of immunogenic domains to the virus-like capsule are capsid proteins of bacterial, plant or animal viruses such as Q, HPV, JCV, HBcAg, cowpea chlorotic mottle virus capsids 35 and many others, nonviral protein compartments such as ferritin, lumazine synthase and encapsulin 31,[36][37][38][39] and de novo designed protein or DNA cages [40][41][42][43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%